Green innovation within moroccan small and medium-sized enterprises: Literature review and questions research - Aberkane Mohammed Saad; Aberkane Otman (Social Sciences and Humanities Open)
The interest in green innovation and its associated concept of sustainable development has increased in recent years. This topic has garnered attention within academic literature, as well as in national and international governmental and non-governmental forums, and think tanks, where discussions regarding environmental issues and the human impact of production and consumption activities have become more prevalent. The objective of this article is to present a comprehensive overview of green innovation and to analyze relevant articles and bibliographic data through a systematic literature review (SLR). A total of 120 articles pertaining to green innovation, published between 2007 and 2024, were selected for review. These articles were categorized based on their respective study areas, with a particular emphasis on industries that encompass multiple sectors, revealing that manufacturing industries constitute the largest segment. This article also identifies applications of green innovation within small and medium-sized enterprises (SMEs) through the systematic literature review. Furthermore, the article proposes and discusses several avenues for future research. The insights provided in this review may be beneficial for universities, organizations, and individuals engaged in corporate research initiatives.